Who likes it "sparkling"? An empirical analysis of Prosecco consumers' profile - Laura Onofri; Vasco Boatto; Andrea Bianco (Agricultural and Food Economics, 2015)
The purpose of the study is to understand the profile (if any) of the typical Prosecco wine consumer, for both Controlled Denomination of Origin (CDO) and Controlled and Guaranteed Denomination of Origin (CGDO) types, with a twofold objective. First, the study aims at contributing to the economics literature dealing with opening the "black box of preferences" and understanding consumers' behavior. Second, more practically, the study aims to advise producers on the design of more targeted industrial strategies and policies. Using Homescan data collected from large-scale retail trade transactions in the period 2009 - 2011, we adopt a probit model and test a set of simple relationships between the probability that Prosecco (in both Geographical Indications) is purchased and selected consumers' socio-economic characteristics and product attributes. The results allow us to draft a profile of the typical consumer of Prosecco. The Prosecco CDO consumer lives in the North of Italy, is wealthy, relatively young, lives in a small (2-3 people) household and reacts to price changes. In addition to the latter feature, the typical Prosecco CGDO consumer has a preference for selected brands and extra-dry wine taste. Marginal effects are computed and predict that a 1% increase in Prosecco CDO price will decrease the probability that a consumer purchases the product by 0.36%. In addition, a 1% increase in Prosecco CGDO price will decrease the probability that a consumer purchases the product by 0.26%. The different sensitivity to price changes is corroborated by the fact that Prosecco CGDO consumers express a preference for the product characteristics (brand and taste) and might be more "loyal to the product" than Prosecco CDO purchasers. Further research will broaden the scale of analysis and adopt multinomial probit models in order to simultaneously assess the profile of different consumers for other types of sparkling wines, including Champagne and Franciacorta.
Keywords: 330